Pengaruh Media Pembelajaran Berbasis Teknologi dan Motivasi Berprestasi terhadap Kreativitas Siswa Jurusan Tata Kecantikan SMKN 2 Boyolangu Tulungagung Tahun Akademik 2024/2025: Penelitian - Ardhea Pregita Pramesti; Ekbal Santoso (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study was conducted to analyze the extent of the influence of utilizing technology-based learning media and achievement motivation on the creativity of students in the Beauty Program at SMKN 2 Boyolangu Tulungagung for the 2024/2025 academic year. This research employed a quantitative approach with a correlational design, involving 108 students selected as samples using the stratified random sampling technique from a total population of 436 students. Data collection was carried out through the distribution of questionnaires that had previously undergone validity and reliability testing. The collected data were then analyzed using multiple linear regression to test the proposed hypotheses. The analysis results revealed that: (1) the use of technology-based learning media has a significant effect on student creativity, (2) achievement motivation also has a significant influence on student creativity, and (3) both variables simultaneously contribute significantly to enhancing student creativity. The coefficient of determination (R²) value of 33.5% indicates that variations in student creativity can be explained by the two independent variables used in this study.